2018
DOI: 10.1249/jsr.0000000000000494
|View full text |Cite
|
Sign up to set email alerts
|

Energy Availability, Macronutrient Intake, and Nutritional Supplementation for Improving Exercise Performance in Endurance Athletes

Abstract: Endurance athletes use nutritional guidelines and supplements to improve exercise performance and recovery. However, use is not always based on scientific evidence of improved performance, which type of athlete would benefit most, or the optimal dose and timing of a particular supplement. Health professionals that give advice to athletes need to target their recommendations on the energy systems and muscle fiber types used for the athlete's sporting event, the goal of the training block, the time of the compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 29 publications
0
35
0
4
Order By: Relevance
“…Long-distance runners require higher amount of energy and macronutrients (protein and carbohydrate) and micronutrients (minerals such as iron, magnesium, sodium, and potassium) to support energy expenditure and hydroelectrolytes loss during exercise and to lead the recovery of lean mass, electrolytes, and glycogen store [18, 19]. In this study, we observed a low daily intake of energy, carbohydrate, fiber, vitamins B3, B6, and D, calcium, magnesium, and potassium, in marathon runners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-distance runners require higher amount of energy and macronutrients (protein and carbohydrate) and micronutrients (minerals such as iron, magnesium, sodium, and potassium) to support energy expenditure and hydroelectrolytes loss during exercise and to lead the recovery of lean mass, electrolytes, and glycogen store [18, 19]. In this study, we observed a low daily intake of energy, carbohydrate, fiber, vitamins B3, B6, and D, calcium, magnesium, and potassium, in marathon runners.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional strategies that provide energy demands and sufficient specific macro- and micronutrients to support the immune function could avoid consumption of “immune boosting” supplements. Endurance athletes usually make many nutritional mistakes, not based on metabolic scientific evidence, mainly regarding which type of athlete would benefit, or the dose and timing [18].…”
Section: Introductionmentioning
confidence: 99%
“…Here, the evidence that the gut microbiome may be a predictor of athletic performance is reviewed. Personalized sports nutrition has incorporated the type of sport or activity, the training status of the individual, the athlete's goals, the time of the competitive season, and the athlete's food preferences (120,121) as well as biological traits such as genetic polymorphisms, RNA expression, and epigenetic modifications (28)(29)(30)(34)(35)(36)(37)(38) in the attempt to optimize athletic performance and response to training programs.…”
Section: Personalized Sports Nutrition and The Potential Effect Of Thmentioning
confidence: 99%
“…13 Sporcu beslenmesi, yüksek karbonhidrat tüketiminin önerildiği diyet programlarını içerir ve karbonhidrat ağırlıklı diyet programı ağız mikroflorasında hastalıklarından sorumlu olan bakterilerin artışına sebep olduğundan diş çürüğü ile ilişkilidir. 14,15 Beslenme, aynı zamanda tükürük miktarını ve tükürük akış oranını da etkiler. 16 Tükürük akış oranı cinsiyete göre de farklılık gösterebilmektedir.…”
unclassified